The preventive and carcinogenic effect of metals on cancer: a systematic review - Amir Hossein Khoshakhlagh; Mahdiyeh Mohammadzadeh; Agnieszka Gruszecka-Kosowska (BMC, 2024)
Abstract Background Many studies have investigated the role of metals in various types of malignancies. Considering the wide range of studies conducted in this field and the achievement of different results, the presented systematic review was performed to obtain the results of investigations on the prevention and occurrence of various types of cancer associated with metal exposures. Methods In this review, research was conducted in the three databases: Scopus, PubMed, and Web of Science without historical restrictions until May 31, 2024. Animal studies, books, review articles, conference papers, and letters to the editors were omitted. The special checklist of Joanna Briggs Institute (JBI) was used for the quality assessment of the articles. Finally, the findings were classified according to the effect of the metal as preventive or carcinogenic. Results The total number of retrieved articles was 4695, and 71 eligible results were used for further investigation. In most studies, the concentration of toxic metals such as lead (Pb), chromium (Cr (VI)), arsenic (As), cadmium (Cd), and nickel (Ni) in the biological and clinical samples of cancer patients was higher than that of healthy people. In addition, the presence of essential elements, such as selenium (Se), zinc (Zn), iron (Fe), and manganese (Mn) in tolerable low concentrations was revealed to have anti-cancer properties, while exposure to high concentrations has detrimental health effects. Conclusions Metals have carcinogenic effects at high levels of exposure. Taking preventive measures, implementing timely screening, and reducing the emission of metal-associated pollutants can play an effective role in reducing cancer rates around the world.